2007
DOI: 10.1074/jbc.m702963200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Laminin Terminal Globular Domains in Basement Membrane Assembly

Abstract: Laminins contribute to basement membrane assembly through interactions of their N-and C-terminal globular domains. To further analyze this process, recombinant laminin-111 heterotrimers with deletions and point mutations were generated by recombinant expression and evaluated for their ability to self-assemble, interact with nidogen-1 and type IV collagen, and form extracellular matrices on cultured Schwann cells by immunofluorescence and electron microscopy. Wild-type laminin and laminin without LG domains pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
236
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(242 citation statements)
references
References 37 publications
4
236
2
Order By: Relevance
“…14,15 In addition, collagen type IV has been shown to be present in the intima of fatty streaks and in advanced lesions. 16 Collagen type IV interaction to endothelial cells is important for maintaining endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 In addition, collagen type IV has been shown to be present in the intima of fatty streaks and in advanced lesions. 16 Collagen type IV interaction to endothelial cells is important for maintaining endothelial cell function.…”
Section: Discussionmentioning
confidence: 99%
“…The LN domains appear to require their adjacent LE repeats to fold properly because of an unusual interdomain pattern of disulfide-binding (Kalkhof et al 2008). Studies with laminin-111 have revealed that selfassembly is calcium-dependent and mediated by cooperative binding among a, b, and g subunit LN domains to form ternary complexes among adjacent laminins (Yurchenco and Cheng 1993;McKee et al 2007) (see Fig. 3A).…”
Section: Laminin Polymerization and Ln-domain Bindingmentioning
confidence: 99%
“…The intercomponent binding interactions and polymerizations of laminins and type IV collagen that create a relevant scaffold matrix were first identified and characterized by a study of purified components in vitro. Assembly on cells, however, has been found to be facilitated by anchorage to select cell surfaces that serves to increase the local surface concentration of components, promoting the interactions (Kalb and Engel 1991;Li et al 2005b;McKee et al 2007). This initial anchoring interaction appears to occur primarily through the laminin LG domains (Figs.…”
Section: Basement Membrane Self-assembly and Receptor Interactionsmentioning
confidence: 99%
See 2 more Smart Citations